Glutathione‐S‐transferase‐oxidative stress relationship in the internal spermatic vein blood of infertile men with varicocele. (28th January 2014) - Mostafa, T.; Rashed, L. A.; Zeidan, A. S.; Hosni, A.
Summary This study aimed to assess glutathione‐S–transferase (GST) enzyme‐ oxidative stress (OS) relationship in the internal spermatic vein (ISV) of infertile men associated with varicocele (Vx). Ninety five infertile oligoasthenoteratozoospemic (OAT) men associated with Vx were subjected to history taking, clinical examination and semen analysis. During inguinal varicocelectomy, GST, malondialdehyde (MDA) and glutathione peroxidase (GPx) were estimated in the blood samples drawn from ISV and median cubital veins. The mean levels of GST, GPx were significantly decreased and the mean level of GPx was significantly increased in the ISV compared with the peripheral blood. The mean level of GST and GPx in the ISV was significantly decreased, and the mean level of MDA was significantly increased in Vx grade III compared with Vx grade II cases. There was nonsignificant difference in the mean level of GST in the ISV in unilateral Vx cases compared with bilateral Vx cases. There was significant positive correlation of GST with sperm count, sperm motility, GPx and significant negative correlation with sperm abnormal forms, MDA. It is concluded that ISV of infertile men associated with Vx has decreased levels of GST compared with peripheral venous circulation that is correlated with both OS and Vx grade.